(untitled) (World Science, 2022)
This article talks about promising ways of development of petrochemical and oil refining industry and efficient use of water resources. Water affects most segments of the petroleum industry, and therefore efficient water management plays a key role in oil and gas exploitation. In most process industries, water is vital to many operations and is used for a variety of purposes such as product preparation, cooling, high purity water makeup water systems, general plant service water, waste handling/conveyance, potable/sanitary service, and fire protection, The water to be managed is produced together with hydrocarbons, formed as a by-product during oil and gas processing. Water has been identified as one of the top four challenges facing the exploitation of one of the largest crude oil fields (oil sands extraction). Large volumes stored in tailings ponds from oil-sand separation must be managed with a long-term view, as dike failure can cause a major environmental disaster.